Hubungan Caring Perawat Berbasis Carative Terhadap Kepatuhan Pasien dalam Pencegahan Diabetic Foot Ulcer pada Pasien dengan Diabetes Mellitus di RSUD Undata Provinsi Sulawesi Tengah: Penelitian - Safia Mayana; Elin Hidayat; Maharani Farah Dhifa Dg Masikki (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Background: Diabetes Mellitus is a chronic metabolic disease characterized by an increase in blood glucose levels due to impaired secretion or insulin action. Prolonged hyperglycemia conditions can cause various serious complications, one of which is Diabetic Foot Ulcer (DFU). DFU prevention is highly dependent on the patient's compliance with self-care, including blood sugar control, foot care, and compliance with recommended therapies. Nurse Caring Behavior has an important role in increasing patient compliance through empathetic communication, emotional support, and providing proper education. The purpose of the research is to analyze the relationship between Carative-based nursing care and patient compliance in the prevention of Diabetic Foot Ulcer at RSUD Undata Central Sulawesi Province. Method: This type of research is quantitative with a cross-sectional approach. The population is 112 people with Diabetes Mellitus at RSUD Undata, Central Sulawesi Province. The sample size is 53 people with the Proportional Quota Sampling technique. The research instrument uses a Curative-based Nursing Care questionnaire and a foot care compliance questionnaire. Data analysis using Fisher's Exact Test Research Results: The research results show that there is a relationship between Carative-based Nurse Caring and patient compliance in the prevention of Diabetic Foot Ulcer at RSUD Undata Central Sulawesi Province with Fisher's Exact Test results obtained Asymp.Sig 0.000 < 0.05. Conclusion: There is a relationship between Curative-based nursing care and patient compliance in the prevention of Diabetic Foot Ulcer at the RSUD Undata Central Sulawesi Province. Suggestion: It is hoped that nurses can improve the implementation of Carative-based Caring in nursing services to improve the compliance of Diabetes Mellitus patients in the prevention of Diabetic Foot Ulcer.